PENGEMBANGAN TUJUAN PENDIDIKAN ISLAM: PERSPEKTIF MUHAMMAD ABDUH - Diana Puspita Kusuma Wardani; Muhammad Arif Syihabuddin (Yayasan An-Nur Meunara Baro, 2026)
This study examines the ideas of Muhammad Abduh regarding the development of Islamic educational objectives as a response to the dualism of education that existed in his time. Abduh criticized traditional education for placing excessive emphasis on memorization and providing limited space for the development of reason, while modern education tended to neglect spiritual values. This research employs a qualitative approach with a library research method. Data were collected through the analysis of Abduh’s works, books, and scholarly journals related to Islamic education. The data analysis technique used is descriptive-analytical. The findings reveal that Muhammad Abduh proposed an integrative educational concept that balances reason and revelation, knowledge and morality, as well as worldly and spiritual life. According to him, the goal of education is to develop individuals who are knowledgeable, morally grounded, rational, and capable of responding to societal changes without abandoning Islamic values. The study concludes that Abduh’s ideas remain highly relevant in contemporary Islamic education, as they bridge the gap between modernity and religious values, although they have been criticized for being overly rationalistic and not fully applicable in practice. This study recommends further development of Abduh’s educational concept in a more contextual and practical manner, so that it can be effectively implemented in the contemporary Islamic education system.